The Deleterious Effect of Victimization on Just World Beliefs. Issue 17 (September 2022) - Catlin, Mary; Scherr, Kyle C.
Being a victim of a violent crime is a traumatic experience. Sexual victimization, in particular, may be powerful enough to change presumably stable worldviews like just world beliefs. Across two large samples, we examined the influence of sexual victimization on just world beliefs. Results of Study 1 ( N = 727) indicated that victims of sexual aggression had significantly lower levels of just world beliefs compared to nonvictims. Other researchers have claimed that sexual aggression is a uniquely intense traumatic event. Therefore, in a second study, we examined (a) whether just world belief endorsement was associated with the frequency of victimization, and (b) whether sexual aggression was unique in its effect on just world belief endorsement compared to other crimes such as physical assault. Results of Study 2 ( N = 2, 011) indicated that multiple incidents of victimization did not meaningfully impact just world beliefs compared to a single instance and just world belief endorsement was not significantly different across victims of sexual aggression, robbery, physical assault, or arson. An exploratory analysis, however, indicated there was a significant difference in victims' behavior such that victims of sexual aggression were the least likely to have reported the crime. We end with a discussion of how the present research can advance our understanding of just world belief ideology and discuss the practical implications for professionals working with and studying victims of violent crimes.